Genetic blueprint of the zoonotic pathogen Toxocara canis - Zhu, Xing-Quan (Nature Pub. Group, 2015)
Toxocara canis is a zoonotic parasite of major socioeconomic importance worldwide. In humans, this nematode causes disease (toxocariasis) mainly in the under-privileged communities in developed and developing countries. Although relatively well studied from clinical and epidemiological perspectives, to date, there has been no global investigation of the molecular biology of this parasite. Here we use next-generation sequencing to produce a draft genome and transcriptome of T. canis to support future biological and biotechnological investigations. This genome is 317 Mb in size, has a repeat content of 13.5% and encodes at least 18,596 protein-coding genes. We study transcription in a larval, as well as adult female and male stages, characterize the parasite’s gene-silencing machinery, explore molecules involved in development or host–parasite interactions and predict intervention targets. The draft genome of T. canis should provide a useful resource for future molecular studies of this and other, related parasites.